The Sacred-Profane Dialectic in Sasak Marriage Rituals: A Phenomenological Analysis of The Merariq Tradition in Lombok, West Nusa Tenggara - Ansharah, Indana Ilma; Mustofa, M Lutfi; Jamilah, Jamilah (JENTRE, 2025)
The Merariq tradition is a typical marriage rite of the Sasak people in Lombok that reflects the combination of traditional values and Islamic teachings. This research aims to examine the dialectic between the sacred and profane dimensions in the Merariq tradition, as well as to understand the transformation of the meaning of the ritual in the midst of the socio-religious dynamics of modern society. The approach used is the religious phenomenology of Mircea Eliade, which emphasizes the concept of hierophany, myth, and rite as a means of interpreting sacred reality. Data were collected through interviews with religious leaders, ritual observations, and literature reviews. The results of the study show that Merariq functions as a rite of passage that affirms the moral cosmos order of the Sasak people through symbols such as Aji Krame. The transformation of the Beseboq ritual shows that there is an effort to harmonize between customary and sharia, where customary practices are purified through the principles of maqāshid sharia. However, the sacredness of Merariq faces serious challenges due to the commercialization of Pisuke (customary money), which has the potential to desacralize marriage and shift its meaning into an economic transaction. This research emphasizes that the integration of customs and sharia needs to be maintained through educational and spiritual approaches, so that Merariq remains a sacred rite that strengthens the morality and spirituality of the Sasak people.